Kepastian Hukum Perubahan Ketentuan Penetapan Bagi Hasil Kontrak Kerjasama Tahap Rencana Pengembangan Lapangan Pada Kegiatan Industri Hulu Minyak Dan Gas Bumi - Abdullah Sholah Syahadah (Riviera Publishing, 2025)
In 2017, the Indonesian government introduced changes to the Gross Split Production Sharing Contract (PSC) system through the enactment of Minister of Energy and Mineral Resources Regulation No. 13 of 2024, which revoked Minister of Energy and Mineral Resources Regulation No. 8 of 2017 and its amendments. The fundamental change in the new Gross Split PSC lies in the assessment of variable and progressive components as adjustments to the profit-sharing provided to Contractors (KKKS). The primary legal issue in this study is the legal certainty of changes in the profit-sharing provisions within the Cooperation Contract (KKS) under the Gross Split scheme for field development plans signed before the enforcement of Minister of Energy and Mineral Resources Regulation No. 13 of 2024. Additionally, there are new obligations for KKKS, such as the use of independent surveyors and the management of unconventional oil and gas, which were not previously included in the KKS. This study aims to examine the legal certainty of changes in the profit-sharing provisions in the Gross Split KKS signed before the regulatory changes, using a normative research method with conceptual, statutory, and case study approaches. The findings indicate that the implementation of the Gross Split PSC requires clear legal certainty in the terms and conditions of the KKS regarding the impact of regulatory changes on previously signed contracts. Thus, there is alignment between the private contractual relationship of the government and private entities while preserving the state’s sovereignty as the holder of oil and gas mining authority.